Incidência, fatores de risco e consequências de defeitos congênitos em recém-nascidos e natimortos - Oliveira, Camila Ive Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Birth defects are observed in around 3 to 5% of newborn babies and most miscarriages and contribute in 50% of spontaneous newborn deaths and thus are considered one of the main causes of infant mortality. Although there have been many studies about birth defects, few have been carried out in under-developed and developing countries and most are hospital based. The objective of this prospective case-controlled population-based study was to analyze all newborns and still-births with birth defects in the municipal of São José do Rio Preto, São Paulo during one year, to identify the types of defects, etiologies, risk factors and consequences. A second objective was to evaluate the official notification of birth defects on the Birth Certificate. The study involved multidisciplinary teams with the participation of all the hospitals of the city in a partnership with the City Health Department. In total 5204 children were studied. Of these, 169 presented birth defects. The data were compared with 169 controls without birth defects. The incidence was 3.2% which corroborates published data. Advanced maternal age, family recurrence of the defect, alcohol ingestion during pregnancy, gestational diabetes and previous miscarriages were some of the most important risk factors. Post-partum hospitalization, hospital costs and death rates of under one-year-old children with birth defects were significantly higher for children with birth defects than for the control group. The under-notification rate of defects in newborn babies of the city was 40.5%. Knowledge about birth defects allows the planning of preventive and therapeutic strategies and adequate public healthcare policies

Defeitos congênitos são observados em cerca de 3 a 5% dos recémnascidos e na maioria das perdas gestacionais, contribuem com 50% das mortes neonatais espontâneas e são considerados entre as principais causas de mortalidade infantil. Embora existam muitos estudos poucos foram realizados em países subdesenvolvidos e em desenvolvimento, e a maioria é de base hospitalar. O objetivo deste estudo caso-controle prospectivo de base populacional foi analisar todos os recém-nascidos e natimortos com defeitos congênitos nascidos no município de São José do Rio Preto/SP, durante um ano, para identificar os tipos de defeitos, etiologias, fatores de risco e consequências. Além disso, avaliar a notificação oficial sobre anomalias congênitas da Declaração de Nascido Vivo. O estudo envolveu equipes multidisciplinares, com a participação de todos os hospitais e parceria com a Secretaria de Saúde do Município. Foram estudadas 5.204 crianças. Destas, 169 apresentaram defeitos congênitos. Os dados foram comparados com 169 crianças controles, sem defeitos. A incidência foi de 3,2%, o que corrobora os dados da literatura. Idade materna avançada, recorrência familial do defeito, ingestão de álcool durante a gestação, diabetes gestacional e abortos anteriores foram alguns dos fatores de risco significantes. As crianças com defeitos congênitos tiveram períodos de internação pós-parto, custos hospitalares e taxa de óbito em menores de um ano de idade significativamente mais elevados do que as do grupo controle. A presença de defeitos congênitos em recém-nascidos do município foi subnotificada em 40,5% dos casos. O conhecimento sobre anomalias congênitas possibilita estratégias preventivas e terapêuticas
Keywords: Genetica humana; Anomalias humanas; Mortalidade infantil; Aconselhamento genetico; Human genetics; São José do Rio Preto Recém-nascido Mortalidade